Profil Tekanan Darah Masyarakat pada Pemeriksaan Kesehatan di Desa Sukarasa Kecamatan Salawu kabupaten Tasikmalaya - Ali Ismail; Surya Gumilar; Irma Fitria Amalia (Lembaga Pengabdian kepada Masyarakat Institut Pendidikan Indonesia Garut, 2019)
Community service is one of the tri dharmas of higher education that must be routinely carried out by a lecturer. One form of community service implementation is to provide services in the health sector through free medical examinations and direct drug consultations to the community. The health check activity this time is to check people's blood pressure. Blood pressure check was chosen because it is a degenerative disease that many suffer. High blood pressure (hypertension) if left untreated can lead to fatal complications such as stroke (51%) and coronary heart disease (45%). This community service aims to provide free health check services to assist the community in health control. This activity is a form of increasing public awareness of the importance of health. This service is descriptive which aims to describe the blood pressure profile of the community. The method used begins with the lecture method to give participants an understanding of what blood pressure is, then checks blood pressure and continues with a consultation. The research was conducted in Susussian Village, Salawu District, Tasikmalaya Regency with a sample size of 66 people. The results of blood pressure measurement showed normal blood pressure in 44 people (66.7%), hypotension 1 person (1.51%), hypertension 21 people (31.8%). Meanwhile, if viewed from gender, hypertension in men (36%) was higher than women (29.2%). From these results it can be seen that some people have a history of hypertension.